A COMPARISON OF THE NIGERIAN ROAD TRAFFIC CRASH REPORT FORM WITH OTHER SELECTED COUNTRIES - ABDULRAHMAN, SULEIMAN; ADEMOLA, IBRAHIM KAMORU; ROGO, KABIRU USMAN; AHMAD, ABDUL-BASIT SA’EED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Road Traffic Crash (RTC) report is the main source of information for any crash database. The preliminary crash report prepared by the Police contains factual information known immediately after the crash. Different agencies use different formats in preparing RTC reports. This paper compares the content of the Nigerian RTC report form with that of other selected ten (10) agencies from developed and developing countries in terms of three (03) traffic-related parameters. The studied RTC forms were from California, Florida, Oregon, Texas, and Louisiana, USA. Others are British Columbia of Canada, Kent of England, Bangladesh, Malaysia, and Sri Lanka. The result shows that information contents vary significantly, and agencies need to readdress the contents and coverage of the necessary information in the forms. In the Nigerian form, there is no clear information on the road surface condition at the crash scene even though the road surface condition (such as Potholes/Patching, Rutting, Hydroplaning or Slippery) contributes to lots of crashes on the Nigerian roads. Also, the forms from Nigeria, Kent County and Sri Lanka can lead to under-reporting of the collision type at the accident scene. Moreover, the information captured in the Nigerian Road Traffic Crash Information Form (RTI 01) is not comprehensive enough in conducting an in-depth investigation and analysis of the accident records. As such the study recommends improving the contents of the form.